Effects of different support conditions on experimental bending strength of thin walled cold formed steel storage upright frames. (November 2018) - Saleh, Ali; Far, Harry; Mok, Lawrence
Abstract: Design computations of industrial storage racks in accordance with current industry standards rely in part on laboratory testing. One of these tests is for determining the bending strength of upright sections. When testing the bending strength about the axis of symmetry of the upright, a four-point bending test of the assembled upright frame is mandated. The test arrangement prescribed by the standard must permit free twisting of the section at the supports, while the applied loads and their reactions for each upright may be applied in the plane of the section's shear centre. A test arrangement that provides free twisting of the upright section at the supports is more complex and difficult to set up compared with a simple support. This paper examines if the condition of free twisting at supports is necessary in the case of shear centre loading, especially that relaxing this particular code requirement would lead to a simpler test arrangement. Laboratory testing of two sets of upright frames, loaded through the upright's shear centre but with each set having a different support condition indicated that free twisting at the supports had no effect on the bending capacity of the upright members tested. The paper outlines the test setup and reports the results in form of characteristic load deformation curves of the tested specimen. Highlights: For determining the bending strength of storage frames, four-point bending test of the assembled frame is mandated. The test arrangement prescribed by the standard must permit free twisting of the section at the supports. Providing free twisting of upright sections at the supports is more complex compared with providing simple supports. The outcomes clearly imply that free twisting at the supports had no effect on the bending capacity of the tested uprighs. It is recommended to consider dropping the free twisting code requirement.